2010
DOI: 10.3389/fneur.2010.00147
|View full text |Cite
|
Sign up to set email alerts
|

The Disturbance of Gaze in Progressive Supranuclear Palsy: Implications for Pathogenesis

Abstract: Progressive supranuclear palsy (PSP) is a disease of later life that is currently regarded as a form of neurodegenerative tauopathy. Disturbance of gaze is a cardinal clinical feature of PSP that often helps clinicians to establish the diagnosis. Since the neurobiology of gaze control is now well understood, it is possible to use eye movements as investigational tools to understand aspects of the pathogenesis of PSP. In this review, we summarize each disorder of gaze control that occurs in PSP, drawing on our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 98 publications
5
98
0
1
Order By: Relevance
“…The video-oculography and ABV analysis confirmed that reduced peak eye velocities are the hallmark of PSP and they are tightly correlated with midbrain atrophy where the excitatory burst neurons responsible for vertical saccades are located [28]. Degeneration of midbrain gaze centers including the mesencephalic reticular formation apparently causes progressive slowing of vertical saccades and may lead to vertical gaze palsy [1].…”
Section: Discussionmentioning
confidence: 99%
“…The video-oculography and ABV analysis confirmed that reduced peak eye velocities are the hallmark of PSP and they are tightly correlated with midbrain atrophy where the excitatory burst neurons responsible for vertical saccades are located [28]. Degeneration of midbrain gaze centers including the mesencephalic reticular formation apparently causes progressive slowing of vertical saccades and may lead to vertical gaze palsy [1].…”
Section: Discussionmentioning
confidence: 99%
“…61 Decreases in saccade velocity and gain account for the most characteristic PSP ocular motor deficits, and have been demonstrated to be highly specific findings that allow differentiation of autopsy-confirmed PSP from other disorders. 26 Profound changes in saccade velocity and gain over the course of one year have been demonstrated in two autopsy confirmed cases of PSP.…”
Section: Biomarkers (Table 1)mentioning
confidence: 99%
“…26 Profound changes in saccade velocity and gain over the course of one year have been demonstrated in two autopsy confirmed cases of PSP. 61 Retinal optical coherence tomography (OCT) may also be a promising biomarker for PSP, but it remains in an early stage of investigation. 62 …”
Section: Biomarkers (Table 1)mentioning
confidence: 99%
“…In that case, it might be baseless to distinguish between fixational and exploratory behaviors. Recent studies have identified abnormal dynamics of saccades and microsaccades as potential diagnostic markers of neurological disease (14)(15)(16); thus, the frame of reference proposed here may have important clinical implications concerning the role of the affected brain centers in the patients' oculomotor behavior.…”
mentioning
confidence: 95%